A mixed-reality approach to soundscape assessment of outdoor urban environments augmented with natural sounds. (May 2021) - Hong, Joo Young; Lam, Bhan; Ong, Zhen-Ting; Ooi, Kenneth; Gan, Woon-Seng; Kang, Jian; Yeong, Samuel; Lee, Irene; Tan, Sze-Tiong
Abstract: To investigate the effect of augmenting natural sounds in noisy environments, an in-situ experiment was conducted using a mixed-reality head-mounted display (MR HMD). Two outdoor locations close to an expressway were selected for the experiment. A natural sound (birdsong or stream) along with a hologram (sparrow/fountain or loudspeaker) was projected through the MR HMD. Participants were asked to adjust the natural sound levels to their preferred level under ambient traffic noise conditions at each location. Participants also assessed the perceived loudness of traffic (PLN) and overall soundscape quality (OSQ) in conditions with and without the augmented natural sounds. The results showed that both natural sounds significantly reduced the PLN and enhanced the OSQ. No significant differences in subjective responses were found between the loudspeaker and visual representations of the natural sound source as holograms. Analysis on the preferred signal-to-noise ratio (SNR), i.e. ratio of natural sound to traffic levels, indicated a strong negative correlation between the preferred SNRs and ambient traffic noise levels. Overall, the preferred SNR of the birdsong was significantly higher than that of the water sound. Among the acoustic parameters tested, the A-weighted traffic noise level was the strongest predictor for the preferred SNR of both the birdsong and water sound. However, the correlation for the water sound was relatively higher than the birdsong. This was due to the larger variance in the subjective evaluation for the birdsong. Graphical abstract: Image 1 Highlights: The preferred SNRs of the in-situ MR approach were 5 dB higher than prior lab tests. As traffic levels increase above 71 dB, softer natural sounds were preferred. A-weighted traffic noise SPL best predicted the preferred SNR of natural sounds. Overall preferred levels of birdsong were 5 dB higher than water sound. There was no difference in the results between natural source and speaker holograms.